The Importance of ‘Manualised Psychotherapy Practice’ in Community Mental Health Care: A Clinical View Point - Olubokun, Jibowu (International Journal of Criminology and Sociology, 2016)
There are many varieties of psychotherapy used in community mental health care such as Cognitive behaviour therapy, dialectical behaviour therapy, group therapy, family therapy and solution focused therapy to name a few. In the current practice environment ' manualised psychotherapy ' is becoming increasingly popular amongst health care practitioners because of the reduced budgets and the need for regular reviews of commissioning arrangements. There is also the need to produce more evidence based interventions with measurable and deliverable clinical outcomes to enhance the overall quality of health care. This is with a view to provide an efficient and a cost effective community mental health service. Some of the inherent advantages of ‘manualised psychotherapy’ are that it promotes 'consistency of approach ' in the sessions and that it facilitates the Internal validity of the data so obtained and minimises the effect of the impact of the therapist on the outcomes. It also constitutes the core of Randomised controlled Clinical trials and thereby helps to compare the efficacy of different psychological therapeutic interventions. it is seen as a link between research and clinical practice. Some of the disadvantages are that it is too regimented, inflexible and limits creativity and that it is an 'ivory tower concept ' which is not in touch with the reality of every day practice in community mental health care. In conclusion the popularity of ‘manualised psychotherapy’ in clinical practice is a welcome development and is a useful addition to the armamentarium of the health care practitioner in providing an efficient and cost effective service.